(-)-AMPELOPSIN A : A DIMER RESVERATROL FROM Dryobalanops oblongifolia (dipterocarpaceae) - Nanik Siti Aminah; Sjamsul Arifin Achmad; Masatake Niwa; Yana Maolana Syah; Euis Holisotan Hakim (Universitas Gadjah Mada, 2006)
A dimer resveratrol compound named (-)-ampelopsin A was isolated from acetone extract of the stem bark of Dryobalanops oblongifolia (Dipterocarpaceae). The structure of this compound was determined on the basis of NMR spectroscopic data.